Profil pasien glaukoma di Poliklinik Mata Rumah Sakit Indera Provinsi Bali Periode Januari 2014-Juni 2015 - Luh Wira Pusvitasari; Anak Agung Mas Putrawati Triningrat (Universitas Udayana, 2018)
Glaucoma is an eye disorder in the form of a chronic neuropathy that characterized by concaving of optic disc, narrowing of visual field, and usually accompany by increasing of intraocular pressure. Glaucoma is the second lead of blindness in the world after cataract. The objective of this research is to study the profile of glaucoma patient based on range of age, gender, glaucoma classification, eye’s involvement, and intraocular pressure in Eye Polyclinic of Indera Hospital of Bali Province in period January 2014- June 2015. This research used a cross-sectional study approach. Medical reports of glaucoma patient in Eye Polyclinic of Indera Hospital of Bali Province in period January 2014 –June 2015 were used as sample. This research was conducted in 3 months, from April until July 2015. Data that obtained then analyzed by descriptive analysis to find the proportion of each variable in sample. Based on the research, found that the number of glaucoma patient in period January 2014- June 2015 is 64 persons, with eye involvement of 78 eyes. Most of them (51%) were in the 40-64 year age group. The gender are mostly men (70%) with secondary glaucoma (37%) dominating the cases. Based on the eyes involved and intraocular presure, unilateral eye (44%) and intraocular pressure ?21 mmHg (36%)are leading the cases. The conclusion of this study is the most prevalence obtained in the age group 40-64 years, the most sex is male, type of glaucoma most is secondary glaucoma. The most involved eye is unilateral (left eye or left oculus) and most abundant intraocular pressure is ?21 mmHg in the left eye. From the profile of glaucoma patient in Eye Polyclinic of Indera Hospital of Bali Province, hope that in the future there will be further counseling about early detection of glaucoma, because glaucoma is the second lead of blindness in the world, and it is irreversible blindness. Keywords: Glaucoma, Glaucoma Classification, Intraocular Pressure